2015
DOI: 10.3892/ol.2015.3355
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of MAL gene expression is associated with colorectal cancer metastasis

Abstract: Abstract. Mal, T-cell differentiation protein (MAL) is a candidate tumor suppressor gene that functions in membrane trafficking processes in polarized epithelial cells. The aim of the present study was to determine its clinical significance in colorectal cancer (CRC). The RNA and protein expression levels of MAL in 30 colorectal specimens were detected by semi-quantitative polymerase chain reaction and immunohistochemistry analysis. Statistical analysis was performed using SPSS software. The RNA level of MAL w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…The results reported in Table S7 showed that high HIF-1a expression is negatively correlated with most of the markers of T cells, CD8 T cells, cytotoxic lymphocytes, NK cells, myeloid dendritic cells cell types (Pearson r < 0 and p value < 0.05, Table S7 ), and positively correlated with most of the makers of monocytic lineage, neutrophils, endothelial cells and fibroblasts (Pearson r > 0 and p value < 0.05, Table S7 ). Within the set of significantly correlated immune markers in Table S7 , we found that MAL, BANK1, CXCR2, and KCNJ15 genes have been previously reported to play a tumor suppressive role in different types of cancer [ 93 , 94 , 95 , 96 ]. These findings support the results shown in Figure 6 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The results reported in Table S7 showed that high HIF-1a expression is negatively correlated with most of the markers of T cells, CD8 T cells, cytotoxic lymphocytes, NK cells, myeloid dendritic cells cell types (Pearson r < 0 and p value < 0.05, Table S7 ), and positively correlated with most of the makers of monocytic lineage, neutrophils, endothelial cells and fibroblasts (Pearson r > 0 and p value < 0.05, Table S7 ). Within the set of significantly correlated immune markers in Table S7 , we found that MAL, BANK1, CXCR2, and KCNJ15 genes have been previously reported to play a tumor suppressive role in different types of cancer [ 93 , 94 , 95 , 96 ]. These findings support the results shown in Figure 6 .…”
Section: Resultsmentioning
confidence: 95%
“…Because the tumor suppressing/promoting role of several immune markers remains controversial to date, we also assessed the potential suppressive role of the immune markers significantly correlated with HIF-1a. Bibliographic search evidenced that MAL, BANK1, CXCR2, and KCNJ15 genes play a tumor suppressive role in different types of cancer, including colorectal cancer, B-cell lymphoma, and renal cell carcinoma [ 93 , 94 , 95 , 96 ]. However, we did not find any study reporting the tumor suppressive role of these genes in NB.…”
Section: Discussionmentioning
confidence: 99%
“…The function of MAL in tumor cells is still controversial. In particular, a tumor suppressor activity was demonstrated in esophageal tumors [ 33 ], as well as in colorectal and gastric cancer [ 34 , 35 ], while an intense MAL protein expression was detected in specific types of renal carcinoma and in thyroid follicular cell-derived carcinoma [ 36 ]. Moreover, MAL was found frequently hypermethylated in colon and breast cancer, thus explaining its reduced gene expression [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mal (myelin and lymphocyte protein, T-cell differentiation protein) is a tumor-suppressor gene and a diagnostic biomarker for colorectal cancer due to its inactivation by promoter hypermethylation [ 21 ]. A recent study reported that Mal downregulation is associated with colorectal cancer metastasis [ 22 ]. Hypermethylation of the Mal promoter is also found in gastric cancers, suggesting that detection of Mal methylation could be a good prognostic marker for other types of cancer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%